SALURAN TERBUKA - Lutjito Lutjito (Universitas Negeri Yogyakarta, 2005)
ABSTRACTThe sediment suspension phenomena have a close something to do withthe watering field, the complexity of the existence of silt particles and clay in afluida which are continuously interact and the turbulence which was happenedhas a specific characteristic.The problems on the sediment suspension flow on the open channel wereapproached with experimental method, i.e. by conducting a direct measurementof the sediment recirculating flume in Hydrology and Hydraulics Laboratory inPAU UGM. To measure the concentration profile of sediment suspension carriage,it is used optical silt measuring instruments type Foslim-probe tools, while tomeasure the flow speed profile, it is used electromagnetic flowmeter probe settype VM-201 H tools and vector calculate equipment type DV-101 tools.From the measurement of 10 series of uniform flow suspensed sediment, itshows that the integration constant value, Br, from logaritmic rule tends to besmaller compared with the integration constant value, Br for pure water, i.e. Br=9. 110 +- 0.734. the integration constant value is affected by the sedimentsuspension concentration level which is showed by the fact that the raisingconcentration will cause the reduction of Br value. From the result of thecomputation, it shows that the coles wake parameterP for the suspensed uniformflow is P =0.085 with the constant value of Von Karman k =0.40 constant. Itshows that te sediment suspension effect will cause the value of P will be moreoppened, it is aggree with the result gained by Coleman (1986) which was saidthat the sediment suspension will cause the greater P value.Keywords: sediment suspension, uniform flow, open channel